Instalment sales in Islamic law: theory and practice - Al-Shalhoob, Salah Fahd (University of Edinburgh, 2009)
This thesis is a study of installment sales according to Islamic law. It is divided into four parts. The first part introduces contracts in Islamic law. The second part discusses the concept, cornerstones and conditions of installment sales. The third part discusses four types of contract: deferred sales, mark-up sales, 'Ina sales and tawarruq sales. Then, the last part discusses organised tawarruq. The first part is an introduction to contracts in Islamic law. Such contracts are divided into two broad categories. The first category is permissible contracts in general according to Islamic law, including contracts of sales, partnerships, leases and loans; these are discussed in the first category. The second category introduces the category of prohibited contracts according to Islamic law; the category includes usury, gharar and cheating. The second part is divided into two sections. The first section focuses on the concept of installment sales. It discusses the linguistic definition of taqsit which literally means installment in Arabic, then it explains the meaning of tanjim as a term of traditional Islamic fiqh, and discusses how scholars use it in some schools of traditional Islamic fiqh, to show the closeness to the meaning of installment. The cornerstones of sales according to traditional Islamic fiqh in general are explained, because installment sales are a type of sales contracts. Then, the conditions of sales according to traditional Islamic fiqh are explained, both in general, and for installment sales contracts in specific. The third part examines the ruling on four types of contract: deferred sales, mark up sales, 'ina sales and tawarruq sales. These four types of contract are relevant to installment sales because they include deferred payment, with the exception of mark up sales, which may or may not include deferred payment, depending on their form. The thesis discusses some rules related to these contracts, including the definitions, the scholars' views, their forms and so on. Lastly, the fourth part focuses on organised tawarruq according to Islamic law. The part is divided into two sections. The first introduces the development of Islamic financial institutions, including early Islamic financial practice, modem Islamic financial institutions approaches towards interest-free banking, current Islamic financial institutions and products of Islamic financial institutions. The second section focuses on organised tawarruq as it is practiced in the financial institutions in Saudi Arabia, as a product to which Islamic law is applicable. The concept, examples, cornerstones and conditions of organised tawarruq are discussed, and a comparison is drawn with organised tawarruq on the one hand, and tawarruq sales and rna sales on the other hand, according to the concept of Islamic business transactions in Islamic. At the end, the section discusses organised tawarruq in the view of Islamic law.
Keywords: Culture; Law; Islam